Solar Energy Storage: Liquid Norbornadiene Photoswitches for Solar Energy Storage (Adv. Energy Mater. 18/2018). Issue 18 (25th June 2018) - Dreos, Ambra; Wang, Zhihang; Udmark, Jonas; Ström, Anna; Erhart, Paul; Börjesson, Karl; Nielsen, Mogens Brøndsted; Moth‐Poulsen, Kasper
Abstract : Molecular photoswitches can be used for solar energy storage through daily, weekly or seasonal energy storage cycles. The cover for article number1703401 by Kasper Moth‐Poulsen and co‐workers illustrates a vision for future implementation combining solar energy capture in a liquid molecule system, long term storage and the release of the stored energy for domestic heating applications.